Aberrant reward-related neural activation: Dimensional correlate of binge-eating severity or categorical marker of binge eating?. (May 2023) - Hagan, Kelsey; Datta, Nandini; Stern, May; Bohon, Cara
Abstract: Binge eating (BE) is characterized by consuming an objectively large amount of food in a short period of time and experiencing loss of control over one's eating. The neural underpinnings of monetary reward anticipation and their association with BE severity remain poorly understood. Fifty-nine women aged 18 to 35 ( M = 25.67, SD = 5.11) with a range of average weekly BE frequency ( M = 1.96, SD = 1.89, range = 0–7) completed the Monetary Incentive Delay Task during fMRI scanning. Mean percent signal change within the left and right nucleus accumbens (NAc) during anticipation of monetary gain (versus non-gain) was extracted from a priori-defined functional 5 mm spheres and correlated with average weekly BE frequency. Exploratory voxel-wise whole-brain analyses examined the association between neural activation during anticipation of monetary reward and average weekly BE frequency. Body mass index and depression severity were covariates of non-interest in analyses. Mean percent signal change in the left and right NAc inversely correlated with average weekly BE frequency. Whole-brain analysis revealed no significant associations between neural activation during reward anticipation and average weekly BE frequency. In exploratory case-control analyses, mean percent signal change in the right NAc was significantly lower in women with BE ( n = 41) versus women without BE ( n = 18), but whole-brain analyses revealed no significant group differences in neural activation during reward anticipation. Decreased right NAc activity during monetary reward anticipation may distinguish women with and without BE.